Saccharide-containing conjugates as eco-friendly coupling agents for silica reinforced rubber compounds - Minji Seo; Chanwoo Lee; Donghyuk Kim; Byungkyu Ahn; Gil-Ryeong Lee; Wonho Kim; Sheng Li (Polymer Testing, 2021)
Silica reinforced rubber is used as a tire tread compound due to its desirable viscoelastic properties. To achieve proper silica dispersion in rubber compound, silane-based coupling agents are required. In this study, we synthesize saccharide-containing molecules and investigate their uses as green coupling agents for the development of environmentally friendly tires. Two saccharide conjugates are prepared: maltose-polybutadiene (Mal-PB) by coupling reaction between alkyne-functionalized Mal and azide-functionalized PB; and maltose-cystamine-maltose (Mal-Cys-Mal) by reductive amination of the reducing end of Mal. Both conjugates are used in place of bis(triethoxysilylpropyl)disulfide (TESPD) for rubber compounding. We find that Mal-PB serves as a good compatibilizer for silica/rubber interface but cannot bridge silica fillers to rubber chains due to lack of sulfur element. Mal-Cys-Mal shows better potential as a coupling agent. The rubber compound prepared with Mal-Cys-Mal shows increased bound rubber content and improved silica dispersion, and the resulting vulcanizate shows modestly improved viscoelastic properties and much improved tensile properties. Overall both saccharide conjugates reported can effectively enhance silica dispersion in rubber compounds, and the sulfur-containing Mal-Cys-Mal has the potential to replace TESPD as a greener coupling agent for tire tread formulation.